Hubungan antara Kebisingan dengan Stres Kerja pada Pekerja di Rumah Sakit Karunia Kasih - Nur Aisyah Rachman; Fini Fajrini (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The purpose of this study was to analyze the relationship between noise levels and work stress among employees at Karunia Kasih Hospital. This study used a cross-sectional design with a population consisting of all employees in the Front Office, Polyclinic Nurses, and Specialist Doctors. The study sample consisted of 80 respondents selected using total sampling technique. Noise levels were measured using a Sound Level Meter, while work-related stress was assessed using a questionnaire. Data analysis was conducted using the chi-square test with a significance level of α = 0.05. The measurement results indicated that 80% of the work areas had noise levels exceeding the NAB 65 dBA threshold. The Outpatient Corridor area had the highest noise level (83 dBA). A total of 65% of workers experienced moderate to severe work-related stress. There was a significant relationship between noise levels and work-related stress (p-value = 0.001). Age (p-value = 0.024) and length of service (p-value = 0.037) also showed a significant relationship with work-related stress. There is a significant relationship between noise levels and work-related stress among workers at Karunia Kasih Hospital. Efforts to control noise levels and comprehensive stress management programs are needed to protect worker health.